GENEALOGI REVOLUSI PARADIGMA PEMIKIRAN KEISLAMAN NAHDLATUL ULAMA - Tejo Waskito (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2018)
This article tries to track genealogy of the Islamic revolutionary paradigm of thought in NU and its various possibilities have arisen. Based on the library studies using the analytical discourse approach, the result revealed that the genealogy of the Islamic paradigm of NU was born due to the internal and external dialectics bridged by multi-epistemology. Based on the 'political reconciliation' event which is called 'returning to khittah 1926' in Situbondo in 1984, NU experienced a shift orientation, not only in the political sphere but also paradigmatically. Hereby, there was social-intellectual mobility marked by the proliferation of social and intellectual discourse among NU’s young generation. The dominance of this activity leading to revolutionary movement in the field of NU’s Islamic paradigm: Aswaja's theology which was originally understood as a doctrine became a thinking methodology (manhaj alfikr); expansion of the legal institution's methodology, from qauly to manhajy; and shifting political struggle, from structural political arena to cultural politics. This discourse became massive among Nu’s young generation caused by the support of Abdurrahman Wahid, the ideal figure known as a locomotive of the NU cultural movement.